Figure-4 Patient Positioning Increases Medial Meniscus Extrusion on Ultrasound in Patients With Posterior Medial Meniscus Root Tears of the Knee - Atsuto Hoshikawa, M.D; Haruhiko Nakamura, M.D; Ryota Takei, M.D; Risa Matsumoto, M.D; Kazuo Saita, M.D (Elsevier, 2023)
Purpose: To compare the degree of medial meniscal extrusion (MME) between knees with medial meniscus posterior root tear (MMPRT) and degenerative tears of the medial meniscus using ultrasonography (US) in different limb positions and to identify the findings characteristic of MMPRT. Methods: The study group comprised 25 subjects with MMPRT (group RT), 25 subjects with degenerative medial meniscal tears (group D), and 25 knees with no abnormalities of the medial meniscus (MM) on magnetic resonance imaging (MRI) (group C) whose age was ≥40 years. MME was evaluated using US in the supine, figure-4, feet-dangling, and standing positions. The MME was evaluated by the actual measurement values and the relative values to the MME in the supine position. The differences in the MME among the 3 groups in each limb position were analyzed using one-way analysis of variance. P < .05 was considered significant. Results: The actual MME values were largest in group RT in all 4 limb positions. When changing the limb position from the supine to the figure-4, the actual MME increased from 3.8 ± 0.8 mm to 5.5 ± 1.3 mm in group RT, whereas it decreased from 3.4 ± 1.1 mm to 1.8 ± 1.2 mm in group D, showing the most significant difference in MME of the figure-4 position between the 2 groups (P < .001). In group RT, 88% of knees had the maximum MME in the figure-4 position. In group D, 60% of knees had the maximum MME in the standing position and only 2 knees (8%) had the maximum MME in the figure-4 position. Conclusions: The increase in MME from the supine to the figure-4 position was a characteristic finding of MMPRT but not degenerative tears. Level of Evidence: Level III, case-control study.